1998
DOI: 10.1104/pp.116.4.1351
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Changes in H2O2 and Catalase during Thermotolerance Induced by Salicylic Acid or Heat Acclimation in Mustard Seedlings1

Abstract: Spraying mustard (Sinapis alba L.) seedlings with salicylic acid (SA) solutions between 10 and 500 μm significantly improved their tolerance to a subsequent heat shock at 55°C for 1.5 h. The effects of SA were concentration dependent, with higher concentrations failing to induce thermotolerance. The time course of thermotolerance induced by 100 μm SA was similar to that obtained with seedlings acclimated at 45°C for 1 h. We examined the hypothesis that induced thermotolerance involved H2O2. Heat shock at 55°C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
262
1
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 544 publications
(286 citation statements)
references
References 60 publications
19
262
1
4
Order By: Relevance
“…The H 2 O 2 levels increased minimally during the 3 weeks of experimentation, and tissue levels of H 2 O 2 were not affected by salinity and B treatments. Similar results were reported by Anderson (2002) for hot pepper leaves under salinity stress, and by Dat et al (1998), who found that mustard and pepper leaves under heat stress had elevated. SOD activity, responsible for the elimination of superoxide radicals in cells, however, in our study the activity decreased at 6 dS/m and 30 mg B/kg, but remained higher than the control treatment, 0 dS/m and 30 mg B/kg (Figure 1c).…”
Section: Resultssupporting
confidence: 77%
“…The H 2 O 2 levels increased minimally during the 3 weeks of experimentation, and tissue levels of H 2 O 2 were not affected by salinity and B treatments. Similar results were reported by Anderson (2002) for hot pepper leaves under salinity stress, and by Dat et al (1998), who found that mustard and pepper leaves under heat stress had elevated. SOD activity, responsible for the elimination of superoxide radicals in cells, however, in our study the activity decreased at 6 dS/m and 30 mg B/kg, but remained higher than the control treatment, 0 dS/m and 30 mg B/kg (Figure 1c).…”
Section: Resultssupporting
confidence: 77%
“…HS per se caused a gradual POX activation between 1-7 days in non-infected plants ( Figure 5). This is in accordance with previous reports, where antioxidative enzymes (Almeselmani et al 2006;Reddy et al 2009) and H 2 O 2 (ROS) (Dat et al 1998;Larkindale & Huang 2005;Kotak et al 2007) participated in the conferring of plant thermotolerance and thermoprotection. However, in the later phases after HS, the combined stress of HS and infection was needed for a more pronounced POX activity increase ( Figure 5).…”
Section: Discussionsupporting
confidence: 82%
“…Reported total foliar concentrations of H # O # (100-300 µM) (Rao et al, 1997 ;Dat et al, 1998) often exceed those required to inhibit photosynthesis in isolated chloroplasts through oxidation of the thiol-regulated enzymes (Kaiser, 1979 ;Charles & Halliwell, 1980). The chloroplastic H # O # concentration is maintained much lower than these total tissue levels (Polle, 1997), principally by chloroplastic APX.…”
Section: The Thioredoxin Systemmentioning
confidence: 99%
“…There is controversy over whether catalase has an important role in the hypersensitive response and systemic acquired resistance that can follow pathogen attack (Chen et al, 1993 ;Rao et al, 1997 ;Dat et al, 1998). In maize seedlings, which have higher photorespiratory rates than mature plants ( De Veau & Burris, 1989), enhanced catalase transcripts, protein and activities were associated with decreased chilling-induced oxidative damage (Prasad, 1996).…”
Section: Catalase and Non-photorespiratory H # O # Generationmentioning
confidence: 99%